Inquiry as an opportunity to make things differently in the language classroom - Mendieta Aguilar, Jenny Alexandra (Colombian Applied Linguistics Journal, 2009)
This article presents a pedagogical experience in a female private school in Bogotá with a group of seventh graders, where the English classes became an excuse to start posing questions about issues that affect young girls and women around the world, as it is women discrimination. The study was developed as an innovative pedagogical proposal and used literature as a means to foster students’ inquiry process. This process was made evident through data collection sources such as students’ artifacts, field notes and video-taped sessions. The data analysis revealed that the target language is not a barrier but a resource for students to wonder about the reality that surrounds them.